2016
DOI: 10.1308/rcsann.2016.0064
|View full text |Cite
|
Sign up to set email alerts
|

Elastofibroma dorsi: The clunking tumour that need not cause alarm

Abstract: Introduction Elastofibromas are rare, pseudo-tumours arising at the inferior pole of the scapula that have a characteristic presentation. Due to their tissue of origin and size, they may often be mistaken for soft tissue sarcomas. We present the management of patients diagnosed with elastofibroma at a single institution. Methods Patients diagnosed with elastofibroma between January 1995 and January 2015 were identified from a prospectively maintained histopathology database. Electronic patient records, imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Furthermore, the data from this group showed that the left and right lesions often had different sizes and the right lesions were larger than the left lesions. The maximum diameter of the right lesions ranged between 2cm and 12cm, with a thickness of about 1-6cm; average volume (mean ± standard deviation) was about 143.24 ± 147.80cm 3 . The maximum diameter of the left lesions ranged between 2.5cm and 10cm, with a thickness of about 0.7-6cm; average volume was about 121.59 ± 116.95cm 3 .…”
Section: Elastofibroma Lesion Characteristicsmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, the data from this group showed that the left and right lesions often had different sizes and the right lesions were larger than the left lesions. The maximum diameter of the right lesions ranged between 2cm and 12cm, with a thickness of about 1-6cm; average volume (mean ± standard deviation) was about 143.24 ± 147.80cm 3 . The maximum diameter of the left lesions ranged between 2.5cm and 10cm, with a thickness of about 0.7-6cm; average volume was about 121.59 ± 116.95cm 3 .…”
Section: Elastofibroma Lesion Characteristicsmentioning
confidence: 97%
“…The maximum diameter of the right lesions ranged between 2cm and 12cm, with a thickness of about 1-6cm; average volume (mean ± standard deviation) was about 143.24 ± 147.80cm 3 . The maximum diameter of the left lesions ranged between 2.5cm and 10cm, with a thickness of about 0.7-6cm; average volume was about 121.59 ± 116.95cm 3 . The volumes of the left and right lesions were significantly different (z = 1.000, P < 0.05).…”
Section: Elastofibroma Lesion Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations
“…Male patients make up 10% of all cases and bilateral tumours in a male patient is extremely rare [ 1 ]. Magnetic resonance imaging (MRI) is the imaging modality of choice and surgery usually entails a simple excision due to a low risk of recurrence [ 2 ]. A tissue diagnosis is required to exclude a soft tissue sarcoma or if conservative management is being contemplated [ 3 ].…”
Section: Introductionmentioning
confidence: 99%